Teletandem: Focus on Form and the Development of the Foreign Language Teacher - Fernandes, Aline Mara [UNESP]; Telles, Joao Antonio [UNESP] (Univ Federal Minas Gerais, Fac Letras, 2015)
Teletandem is a virtual autonomous webcam-based context (image, voice and text), where two students help each other learn their native (or other) language through intercultural and linguistic collaboration. In this paper, we turned our attention to episodes of focus on form during a teletandem interaction in Portuguese. The participants were a Brazilian student (a pre-service teacher of English) and her American teletandem partner (a university student of Portuguese). The analysis of this interaction consisted in looking for focus on form episodes that were incidental (they emerged from conversation spontaneously or they were not previously defined by the teletandem partners). The analysis revealed (a) the prevalence of the focus on form concerning lexicon treatment; and (b) fourteen collaborative actions that provided moments of vocabulary explanation between the partners. We conclude with a discussion on teachers' use of metalanguage; in the case of this study, when teaching Portuguese as a foreign language.
Keywords: Focus on form; Teletandem; Foreign language teacher development; Portuguese as a foreign language